2022
DOI: 10.1186/s40814-022-01057-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating and defining outcomes of suprapatellar versus infrapatellar intramedullary nailing of tibial shaft fractures: a protocol for a pilot randomised controlled trial

Abstract: Background Anterior knee pain is often reported following intramedullary nailing of tibial shaft fractures. The aetiology remains unclear, but the surgical approach may play an important role. To date, no biomechanically validated method exists to assess patient outcomes specific to anterior knee pain in this cohort. The central aims of this study are to (1) evaluate the feasibility of a full-scale randomised controlled trial (RCT) investigating the influence of surgical approach on intramedull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
2
0
1
Order By: Relevance
“…Of the 44/152 (29%) studies reporting AKP, only 10/44 (23%) studies reported an accompanying VAS or NRS score (8 and 2 studies, respectively). The use of binary measures alone is problematic as they are unable to distinguish differing degrees of pain, or pain only with certain activities; require large participant numbers for adequate study power [ 41 ]; and are limited in their ability to detect differences between treatments [ 42 ]. Conversely, continuous scales provide a more clinically informative statistic: they enable the calculation of the proportion of patients who achieve a clinically important improvement in pain scores [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 44/152 (29%) studies reporting AKP, only 10/44 (23%) studies reported an accompanying VAS or NRS score (8 and 2 studies, respectively). The use of binary measures alone is problematic as they are unable to distinguish differing degrees of pain, or pain only with certain activities; require large participant numbers for adequate study power [ 41 ]; and are limited in their ability to detect differences between treatments [ 42 ]. Conversely, continuous scales provide a more clinically informative statistic: they enable the calculation of the proportion of patients who achieve a clinically important improvement in pain scores [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients' self-cognition and improve patients' cognitive ability will be reshaped. [40][41][42] Eventually, patients should be guided to find that life not only has immediate difficulties but also unlimited possibilities in the future, change patients' attitude toward life, and greet future life with more enthusiasm. [43,44] The main limitation of this study is that the sample size of the study is small and the follow-up time is short.…”
Section: Discussionmentioning
confidence: 99%
“…Por un lado, el procedimiento puede conducir al desplazamiento proximal del fragmento de fractura con la rodilla en flexión, lo que, en consecuencia, genera valgus y procurvatum, además, se genera inflamación en la extremidad, aumentando el riesgo de síndrome compartimental y alarga la duración quirúrgica [1,5]. Por su parte, es preciso señalar que el dolor postoperatorio en la parte anterior de la rodilla es la complicación más frecuente tras el enclavado tibial, y reporta una incidencia que varía del 10 al 86% de los pacientes [2,[6][7].…”
Section: Introductionunclassified